2003
DOI: 10.1021/ar020269i
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Photoreactions within Zeolites:  Role of Confinement and Alkali Metal Ions

Abstract: In this Account strategies using zeolites as media to achieve chiral induction are presented. Diastereomeric excesses as high as 90% and enantiomeric excesses up to 78% have been obtained with selected systems within zeolites. The same systems show no asymmetric induction in solution. Chiral induction is dependent on the alkali ions present in the zeolites. Alkali ions control not only the extent of asymmetric induction but often the isomer being enhanced. Results of ab initio computations have allowed us to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(152 citation statements)
references
References 30 publications
2
150
0
Order By: Relevance
“…In this methodology, the chiral inductor is bonded directly to the achiral substrate so that each zeolite cavity will contain both substrate and inductor by default. This approach has worked very well in a number of cases and, together with the work on the chiral inductor method, has led to some general observations that may be useful for the intelligent design of systems for asymmetric induction [20,134,135]. It was observed that selectivity was dependent on the nature and number of cations and was reduced in the presence of water, leading to the conclusion that charge-balancing cations play an important role in intrazeolite asymmetric induction.…”
Section: Intrazeolite Asymmetric Photoreactionsmentioning
confidence: 99%
“…In this methodology, the chiral inductor is bonded directly to the achiral substrate so that each zeolite cavity will contain both substrate and inductor by default. This approach has worked very well in a number of cases and, together with the work on the chiral inductor method, has led to some general observations that may be useful for the intelligent design of systems for asymmetric induction [20,134,135]. It was observed that selectivity was dependent on the nature and number of cations and was reduced in the presence of water, leading to the conclusion that charge-balancing cations play an important role in intrazeolite asymmetric induction.…”
Section: Intrazeolite Asymmetric Photoreactionsmentioning
confidence: 99%
“…However, recent studies by Ramamurthy and coworkers showed that the inherently low or negligible diastereoselectivity obtained in solution can be signifi cantly improved by confi ning the same substrate in the supercage of achiral zeolites. 45 Photolysis of tropolone ( S ) -2 -methylbutyl ether 6 (Scheme 4.4 ) in hexane affords a pair of diastereomers 7 as a 1:1 mixture, along with isomeric 8 . Strikingly, the same photoreaction in NaY zeolite at − 20 ° C gave 7 in 68% diastereomeric excess (de).…”
Section: Diastereodifferentiating Photoreactions With Achiral Zeolitementioning
confidence: 99%
“…Results on three systems are highlighted in Scheme 10.22 . 59,69 Generally, higher de is obtained with aryl amides than with alkyl amides as chiral auxiliaries. The important question concerning the reason for the contrasting behavior of the aryl and the alkyl chiral auxiliaries was answered with the help of ab initio computations at the Hartree -Fock level (HF/3 -21G).…”
Section: Role Of Metal Ions In Stereoselective Phototransformations Wmentioning
confidence: 99%